Effect of Yogic Practices on Postural Deformities of Spine: A Systematic Review - Singh, Bhushan; Joshi, Vivek; Deo, Guru (International Research in Medical and Health Sciences, 2023)
Introduction: The Spine or backbone also called the vertebral column is made up segmented series of vertebrae separated by intervertebral discs on top of one another. It houses a spinal canal, a cavity that encloses and protects the spinal cord. When abnormalities of the spine occur, the natural curvatures of the spine are misaligned or exaggerated in certain areas, as occurs with lordosis, kyphosis, and scoliosis. It can affect the spine's ability to do its job, leading to pain, neurological problems, and mobility challenges.Aim: The current review aims to study the effectiveness of yoga therapy in the management of spinal deformities by going through published scientific literatureMethod: The purpose of this review was to review systematically the impact of yogic interventions on postural deformities of the spine. In this review, a total number of 25 published papers from 2010 to 2022 were included and critically reviewed. Randomized control trials, cross-sectional studies, quasi-experimental, retrospective studies, and pilot studies, these study designs were used with the majority being randomized control trials. Results: The number of subjects participating in the studies ranged from 21 to 1245 but most of the studies had a small sample size. The duration of the intervention period varied greatly, with the majority being 4 weeks or longer. Most of the studies had a small duration of intervention carried out to see the effect of selected Yogic practices on chosen parameters. The research was not uniform in intervention but often varying in nature. All the findings were on the different aspects of spinal deformities each requiring an entirely different intervention. Despite the limitations, it can be concluded that the yoga interventions were effective in improving Cobb’s angle and flexicurve angle for the management of lordosis, kyphosis, and scoliosis across all the reported findings. Conclusion: Evidence suggests that yoga is an acceptable and safe intervention, which may result in clinically relevant improvements in pain and functional outcomes associated with a range of musculoskeletal disorders (MSDs). Habitual yoga practitioners showed greater spine health in both sagittal and coronal planes which suggested that long-term practice of yoga is beneficial for spine-related disorders.